Advances in understanding of the interaction between Ceratocystis cacaofunesta and Xyleborus ferrugineus (Coleoptera: Curculionidae: Scolytinae) on cocoa trees - Paladines-Rezabala, Anderson (2022)
Cocoa (Theobroma cacao L.) is one of the main crops in Latin American and African countries, its almonds being marketed to produce chocolate. However, different biotic factors can negatively affect the crop production, especially on small farms where management by farmers is scarce or nonexistent. Lethal wilt (Ceratocystis cacaofunesta Engelbrecht & Harrington) together with beetle borers (Coleoptera: Curculionidae: Scolytinae), continue to be the main problems affecting cocoa. It has been observed that both organisms interact intrinsically inside the trunks of cacao trees. Despite the importance of this interaction, in general, the countless research and review articles carried out to date have focused mainly on studying each biotic factor separately or have been addressed in a general way. Thus, in this review we mainly focus on the interaction between the Lethal wilt and the borer beetles, especially how and which is the insect that transmits the disease in cocoa plants. Additionally, an exhaustive characterization of Xyleborus ferrugineus as a possible vector of C. cacaofunesta in cacao trees has been made. From this review, we can say that Ceratocystis species still need to be fully identified and differentiated, a deeper understanding of the ecology of the scolithid X. ferrugineus, to study the interaction between C. cacaofunesta and vectors from the host response and generate new studies, and the chemical ecology of the fungus-vector-tree still needs to be understood.